Morfologi av blockiga semialluviala vattendrag: experimentell strömränna-studie för att modellera vattendrag i norra Fennoskandia - Polvi, Lina (Swedish National Data Service, 2020)
In northern Fennoscandia, semi-alluvial boulder-bed channels with coarse glacial legacy sediment are abundant and due to widespread anthropogenic manipulation during timber-floating, unimpacted reference reaches are rare. The landscape context of these semi-alluvial rapids— with numerous mainstem lakes that buffer high flows and sediment connectivity in addition to low sediment yield— contribute to low amounts of fine sediment and incompetent flows to transport boulders. To determine the morphodynamics of semi-alluvial rapids and potential self-organization of sediment with multiple high flows, a flume experiment was designed and carried out to mimic conditions in semi-alluvial rapids in northern Fennoscandia. Two slope setups (2% and 5%) were used to model a range of flows (Q1, Q2, Q10 & Q50) in a 8 x 1.1 m flume with a sediment distribution analogous to field conditions; bed topography was measured using structure-from-motion photogrammetry (SfM) after each flow to obtain digital elevation models (DEMs). Ground-based LiDAR was used to obtain control points needed to create the SfM-based DEMs. The DEMs have a resolution of 5 x 5 mm; separate DEMs are shown for initial conditions at each slope and after each flow. Exported sediment after the 2% slope flows was replaced into the flume and the bed was mixed to create similar initial plane bed conditions before the 5% slope flows as with the 2% slope setup. Shapefiles of digitized grains > D84 are also included. These were created based on the initial conditions for each slope separately. Analyses of the DEMs were done by creating DEMs-of-difference (DODs) by subtracting DEMs from one another to obtain elevation changes. These elevation changes were analyzed for the entire flume an in relation to >D84 grains. Results of these analyses have implications for restoration of gravel spawning beds in northern Fennoscandia and highlight the importance of large grains in understanding channel morphodynamics. A mobile-bed physical model of the semi-alluvial ...